Analysis of the Relationship between Certain Biokinematic and Goniometric Variables of the Linear Smash with Explosive Force Upwards, Forwards, and in Volleyball Shooting - Tariq Ismael, Ayad (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2024)
Linear smash, a potent offensive weapon in volleyball, demands complex biomechanical coordination and techniques. This study aimed to identify the biokinematic and goniometric variables of a linear smash and explore their relationship with explosive strength during performance. The research sample comprised 11 female volleyball players from the Sanharib Club. Physical tests measured explosive strength through vertical/forward jumps and medicine ball throws. The biokinematic variables included center of mass elevation/displacement, arch depth, movement time, and velocities. Goniometric variables measured the joint angles during execution. The video analysis software extracted variable values during players' smash attempts. Key findings revealed significant inverse correlations between explosive vertical jump strength and horizontal center-of-mass distance (-0.911) and between explosive medicine ball throw strength and horizontal distance (0.891). Additionally, a positive correlation existed between medicine ball throw strength and shoulder joint angle at the maximum arch (0.82). The vertical center of mass elevation was inversely correlated with the forward jump distance (-0.776). Strong but insignificant relationships emerged between variables such as horizontal speed/medicine ball throw and takeoff-landing distance/jump time. The results highlight the importance of the explosive strength for upward/forward propulsion and proper joint angles for efficient energy transfer during smashing. Recommendations include focusing on correlated variables through targeted training, utilizing joint ranges of motion, and incorporating additional biodynamic factors. This study provides insights into optimizing the linear smash through biomechanical analysis and training interventions.